Analysis of Science Learning Module Development Needs PBL-Based (Problem Based Learning) to Improve HOTS - Azahro, Milatun Nafiah; Agnafia, Desi Nuzul (Science Education and Application Journal, 2022)
This study aims to examine the needs of students in MTs Negeri 2 Ngawi, especially Class VII, for PBL-based science learning modules to improve HOTS. This development research method is R&D (Research and Development), which is adapted from the development of a 4-D model (Define, Design, Develop and Disseminate). However, this research is limited to the Define stage, which is carried out by analyzing learning procedures. The subjects of this study were MTsN 2 Ngawi science teachers and class VII students who had studied temperature and heat material. Based on the questionnaire from students, it can be concluded that 90% of students believe in the need to develop teaching materials. While the questionnaire given to teachers found the result that learning in the classroom seemed to be monotonous so that it did not support the ability of students to think at a high level, it was necessary to have teaching materials or modules as support because the books provided by the government were inadequate. In conclusion from the results of the questionnaire of students and teachers, as well as the cognitive learning outcomes of students, it is necessary to develop modules related to Temperature and Heat. The development of problem-based learning modules (PBL) is a method for teachers to improve the learning process of students, especially in terms of fostering higher-order thinking skills (HOTS).